EVALUATION OF INNER SEGMENT-OUTER SEGMENT JUNCTION INTEGRITY BY OCT IN PATIENTS OF BLUNT OCULAR TRAUMA AND THEIR CORRELATION WITH VISUAL ACUITY - KHYATI NIRAPURE; BIMALESH OJHA; VIKAS JAMRA; ANKIT SOLANKI (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The aim of this study was to find the prevalence of inner segment-outer segment (IS-OS) junction changes in the foveal region in patients of blunt ocular trauma. Methods: A cross-sectional observational study was done in department of ophthalmology in tertiary health care center, Rewa (M.P.), India from January 2020 to September 2021 with 80 patients of blunt ocular trauma. HD-5line raster with enhanced depth imaging was done for each eye using Cirrus HD optical coherence tomography machine and results were obtained. Results: The mean age of the patients undergoing blunt ocular trauma was 36.59±16.26 years. Out of 80 patients 61 were male and 19 were female. Twenty-nine patients had posterior segment involvement out of which 25 had IS-OS junction disruption. Conclusion: There is high prevalence of IS-OS junction changes in the foveal region in patients of blunt ocular trauma with posterior segment involvement and has a significant correlation with visual acuity.